On the number of invariant polynomials of the product of matrices with prescribed similarity classes - Zhang, Yu Lin (1998)
We study the possibilities for the number of nontrivial invariant polynomials of the product of two nonsingular matrices, with prescribed similarity classes, over an algebraically closed field.